Focus perception in Japanese: Effects of lexical accent and focus location. - Albert Lee; Faith Chiu; Yi Xu (PLoS ONE, 2022)
This study explored the contexts in which native Japanese listeners have difficulty identifying prosodic focus. Using a 4AFC identification task, we compared native Japanese listeners' focus identification accuracy in different lexical accent × focus location conditions using resynthesised speech stimuli, which varied only in fundamental frequency. Experiment 1 compared the identification accuracy in lexical accent × focus location conditions using both natural and resynthesised stimuli. The results showed that focus identification rates were similar with the two stimulus types, thus establishing the reliability of the resynthesised stimuli. Experiment 2 explored these conditions further using only resynthesised stimuli. Narrow foci bearing the lexical pitch accent were always more correctly identified than unaccented ones, whereas the identification rate for final focus was the lowest among all focus locations. From these results, we argue that the difficulty of focus perception in Japanese is attributed to (i) the blocking of PFC by unaccented words, and (ii) similarity in F0 contours between lexical pitch accent and narrow focus, including in particular the similarity between downstep and PFC. Focus perception is therefore contingent on other concurrent communicative functions which may sometimes take precedence in a +PFC language.